THEORETICAL ASPECTS OF PREDISPOSITION TO DYSLEXIA IN OLDER PRESCHOOL CHILDREN - Maksudova Aziza Alisherovna; Morkhova Inessa Vyacheslavovna (American Journals, 2024)
This article explores the theoretical aspects of predisposition to dyslexia in older preschool children. It defines dyslexia as a neurological condition related to difficulties in reading and writing. The article examines the factors influencing the development of dyslexia in preschool-aged children, including genetic, cognitive, and environmental factors. It also discusses the early signs of dyslexia that can be observed during the preschool years and emphasizes the importance of early detection and intervention.
Keywords: Dyslexia, preschool children, predisposition, early detection, cognitive factors, genetic factors, environmental factors, educational development.